دراسة قياسية لأثر الضغوط التضخمية المستوردة على الواردات الجزائرية خلال الفترة (2000-2021) باستخدام طريقة Ardl - شويرفات عبد القادر; حميداتو نصر (جامعة الوادي University Of Eloued, 2024)
This study aims to investigate the relationship between inflationary and imported pressures and the value of Algerian imports. The study uses annual data for the period (2000-2021), in order to reduce its continuous negative effects on the purchasing power of the Algerian citizen. The results of the unit root showed that all variables are stable at the first difference, and the results showed that there is a short-term and statistically significant integration relationship between imported inflation and the value of Algerian imports, and the non-significance of this relationship in the long term.
An econometric study of the impact of imported inflationary pressures on Algerian imports during the period (2000-2021) using the ARDL method
Keywords: تضخم مستورد; واردات; انحدار ذاتي للفجوات المبطأة; imported inflation; imports; auto-regressive lagging gaps (ARDL)